2023
DOI: 10.3390/su15086436
|View full text |Cite
|
Sign up to set email alerts
|

Digital Financial Inclusion, Land Transfer, and Agricultural Green Total Factor Productivity

Abstract: Improving agricultural green total factor productivity is important for achieving high-quality economic development and the SDGs. Digital inclusive finance, which combines the advantages of digital technology and inclusive finance, represents a new scheme that can ease credit constraints and information ambiguity in agricultural production. First, this study focused on agro-ecological functions; we incorporated total agricultural carbon sequestration and emissions extraction into the evaluation system and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 72 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Some studies analyzed provincial panel data in China and confirmed that digital inclusive finance drives the growth of green agricultural TFP. They reported that digital inclusive finance enhances agricultural green TFP by optimizing the structure of the agricultural industry [22], stimulating agricultural technological innovation [23,24], and promoting the marketization of rural land transfer [25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies analyzed provincial panel data in China and confirmed that digital inclusive finance drives the growth of green agricultural TFP. They reported that digital inclusive finance enhances agricultural green TFP by optimizing the structure of the agricultural industry [22], stimulating agricultural technological innovation [23,24], and promoting the marketization of rural land transfer [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drawing on the practices used by Zheng and Li (2022) [20] and Shen et al (2023) [25], this study uses a fixed-effects model to analyze how digital inclusive finance affects agricultural TFP. The analysis considers four models: (1) a single-time fixed-effects model, (2) a singlearea fixed-effects model, (3) a two-way fixed effects model without control variables, and (4) a two-way fixed effects model with control variables.…”
Section: Benchmark Regression Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The sixth assessment report of the Intergovernmental Panel on Climate Change (IPCC) states that due to the vulnerability of climate change, the ecosystems that have supported human development in the past, present, and future will be strongly impacted by climate change. Unsustainable agricultural expansion has increased the vulnerability of ecosystems and human beings, despite the fact that agricultural development contributes to food security [1][2][3][4]. According to statistics from the Food and Agriculture Organization (FAO) of the United Nations, agricultural land releases more greenhouse gases than the total global anthropogenic greenhouse gas emissions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches to these concepts attempt to reconcile this paradox and address the dialectic between development and sustainability [4]. Most of the existing studies have focused on sustainable development in specific regions and areas, such as countries, regions, and cities [5][6][7][8][9], and industries, energy, and the environment [10][11][12][13], focusing on the theoretical connotation of sustainable development, the construction of indicators, comprehensive evaluation, influencing factors, and response strategies [8]. For example, at the national level, Madurai Elavarasan et al (2022) developed a new Sustainable Development Goal or Energy Sustainability Composite Index to assess the energy sustainability performance of European countries [14].…”
Section: Introductionmentioning
confidence: 99%